Housing supply and its relationships with land supply. Issue 3 (3rd August 2015) - Gu, Guowei; Michael, Lynne; Cheng, Yapeng
Abstract : Purpose: – This paper aims to explore the determinants of housing supply and the relationships between land supply and housing supply in terms of quantity and time in Shanghai, China. Design/methodology/approach: – Official statistical and property registration data[] from Shanghai are used to carry out multiple linear regression analysis. Findings: – The authors find that land supply affects housing supply with a three-year time lag. Both construction cost and housing price impact supply with a one-year time delay. The construction cost elasticities range from 0.74 to 1.51, while housing price elasticity is 2. The authors also find that plot ratio may play more important role in the developer's first housing sale than either plot area or sales price. An average time period from obtaining the land for residential development until marketing the product is established at 36.8 months. Research limitations/implications: – Only ordinary least squares method is applied in this analysis and the property portal on which this research relies is still at an early stage. Originality/value: – This research contributes to a wider understanding of issues surrounding housing supply in the local markets within China and provides the foundation for local government to better manage supply.